IMPROVING ELEVENTH GRADERS' SPEAKING ACHIEVEMENT THROUGH THE GOGOMO STRATEGY - Asmiranda; Heru Setiawan (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2025)
GOGOMO is a collaborative approach that enables students to engage and practice speaking with each other. This approach allows students to express their thoughts. This research sought to: (1) determine if there was a notable enhancement in the speaking skills of the eleventh-grade students at SMA Negeri 10 Palembang through the GOGOMO strategy, and (2) assess if there was a significant disparity in speaking skills between the eleventh-grade students at SMA Negeri 10 Palembang who learned with the GOGOMO strategy and those who did not. This research employed a quasi-experimental design involving 70 students, who were chosen through purposive sampling. The data were gathered through a speaking assessment. To confirm the hypotheses, the collected data were examined with the Paired Sample T-Test and Independent Sample T-Test. The findings showed that the GOGOMO strategy significantly enhanced the speaking proficiency of eleventh-grade students at SMA Negeri 10 Palembang. Moreover, a notable difference existed in the speaking achievements of the eleventh-grade students at SMA Negeri 10 Palembang between those instructed with the GOGOMO strategy and those who received no such instruction. The experimental group surpassed the control group in terms of speaking performance. The GOGOMO strategy may have created an environment for students to engage with their peers and enhance their speaking skills. When used for a speaking class, GOGOMO needs to be modified or supplemented, even though it might work well for some activities. Alternative approaches that improve engagement while preserving comprehension accuracy should be investigated in future studies.